Gestión de ventas y servicios mediante página web en Clínica Veterinaria Faytong, periodo 2022. - Mora Valverde, Karla Cecibel (2023)
This paper is based on the study of the Sales and Service Management of the Faytong Veterinary Clinic in the city of Babahoyo, which has more than 15 years of experience; therefore, the main objective of this research is to identify through an Ishikawa diagram the effects caused by the lack of automation of the processes. At the same time, the methodology applied was the inductive method, since through observation and analysis, it was possible to identify the flaws in these processes. In addition, an interview was conducted with the owner and a customer survey was conducted to determine that the owner has no knowledge of e-commerce and for this reason does not use the website or invest in it.